Economic efficiency of additional introduction of lysine and methionine to milk replacer for feeding dairy calves - Лисенко, Г. Л.; Бучковська, К. Д. (Scientific Progress & Innovations, 2018)
The effect of additional lysine and methionine management on the growth of calves and milk producers has been studied and economic efficiency has been established. The scientific and economic research was conducted at «Druzhba-Nova» ALLC in Chernihiv region. For the experiment, 6 groups of calves were formed at the age of 3 weeks, with 20 heads in each. The groups were selected according to the principle of para-analogues, taking into account the age, gender and live weight of calves. The conditions for keeping calves of the control group and the subjects did not differ. The calves were fed three times a day. During the whole experiment, calves of the control group received the main diet, animals in experimental groups were fed lysine and methionine in the form of powder mass to the milk replace in the morning feeding. Group I – control, receiving the main diet containing 1.95 g of lysine and 0.49 g of methionine in the milk substitute (per 100 g of milk replacer); in the II and III groups, the content of lysine was 2.24 g and 2.44 g, respectively, the content of methionine in these groups did not change and was 0.49 g; IV–V groups received 0.56 g and 0.61 g of methionine, respectively, and the lysine content did not change from the actual one (1.95 g); VІ group received a collection of lysine and methionine, the content of these amino acids amounted to 2.34 g and 0.59 g, respectively. The economic efficiency of the introduction of lysine and methionine into the diet of dairy calves was determined by calculating feed costs by 1 kg of increment and cost of 1 kg of growth. In order to calculate the cost, prices for the first quarter of 2017 were used. It was established that at the additional introduction of lysine and methionine, the cost of 1 kg of growth in the II, III, IV and V groups was increased by 12.24, 17.30, 28.15 and 3.86 UAH, which in % was 18.6, 26.3, 42.8 and 5.9 respectively. However, it should be noted that the additional addition of lysine and methionine to milk replacer cost less than the cost of 1 kg increase of 2.87 UAH, which is 4.4 %.